The Story Of Ruby Bridges - Robert Coles (U.S.A Scholastic Inc., 1995)
For months, six-year old Ruby Bridges must confront the hostility of segregationists when she becomes the first African American girl to integrate Franz Elementary School in New Orleans in 1960.
Keywords: Biography -- Biography